1988
DOI: 10.1161/01.str.19.6.716
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline in acute nonhemorrhagic stroke. A randomized, placebo-controlled double-blind trial.

Abstract: The efficacy and safety of pentoxifylline were assessed in 297 adult patients with ischemic stroke in a molticenter, doable-blind, randomized and placebo-controlled trial. Treatment was started within 12 hoars after the stroke onset Study medication was administered intravenously continuously (16 mg/kg/day, maximum 1,200 mg/day) for 3 days and per os (400 mg ti.d.) for the remainder of 28 days. Demographic data were comparable, and functional impairment and mortality (pentoxifylline 12%, placebo 10%) were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 30 publications
(17 reference statements)
1
21
0
3
Order By: Relevance
“…430,431 In one trial, pentoxifylline and propentofylline were administered via continuous intravenous infusion over a 3-day period in patients experiencing an acute ischemic event. 432 Other studies continued infusions for 5 days, as in the trial by Chan and Kay in 1993, or 7 days, as in the trial of Huber et al in 1993. 433,434 Early case fatality, defined as within 4 weeks, was evaluated in several trials of pentoxifylline.…”
Section: B Vasodilators In Acute Ischemic Strokementioning
confidence: 99%
See 2 more Smart Citations
“…430,431 In one trial, pentoxifylline and propentofylline were administered via continuous intravenous infusion over a 3-day period in patients experiencing an acute ischemic event. 432 Other studies continued infusions for 5 days, as in the trial by Chan and Kay in 1993, or 7 days, as in the trial of Huber et al in 1993. 433,434 Early case fatality, defined as within 4 weeks, was evaluated in several trials of pentoxifylline.…”
Section: B Vasodilators In Acute Ischemic Strokementioning
confidence: 99%
“…433,434 Early case fatality, defined as within 4 weeks, was evaluated in several trials of pentoxifylline. [432][433][434][435] The trial conducted by Chan and Kay found a large reduction in the odds of early death; however, this was not borne out in other studies. Two trials demonstrated a nonsignificant reduction in early death or deterioration.…”
Section: B Vasodilators In Acute Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Followup was 28 days. The groups did not differ in mortality or functional deficit (Hsu et al, 1988).…”
Section: A Miscellany Of Other Agents Studied Without Success In Largmentioning
confidence: 80%
“…This model accounted for 62% of the observed variation and was based on 11 studies: NIHSS predicted ϭ0.42ϫmaximum ageϪ0. 22 ϫtime window Ϫ20.9…”
Section: Resultsmentioning
confidence: 99%